Analisis Fenomena Hyperhonest Penggunaan Fitur Instagram Close Friends Dalam Batasan Privasi - Orvella Clara Chiquita; Poppy Febriana (Fakultas Ilmu Komunikasi UKWMS, 2023)
ABSTRACT With the development of new social media features that now make social media not only limited to exchanging information, but also used as a space for self-disclosure, one of which is self-disclosure on the Instagram